The Role and Benefits of Innovative Technology in Using The Internet of Things (IOT) Towards Industrial Revolution 4.0 - Devina Nadya Ayu Pramita; Wahyu Sardjono (Dinasti International Journal of Education Management And Social Science, 2024)
In the Industrial Revolution 4.0, technological developments are developing very rapidly and significantly impact various sectors, especially in the industrial sector. Various aspects of the industrial sector significantly influence the Industrial Revolution 4.0 for companies, governments and even levels of society so that they can keep up with the times and compete in the current industrial revolution. The role of Industrial Revolution 4.0 is centred on automation, which is assisted by using information technology in the application process. One way to keep up with the times and compete is by applying the Internet of Things (IoT) to changes in the Industrial Revolution 4.0. IoT applies a system of computerized, mechanical, and machine devices. The Web of Things (IoT) is exceptionally compelling in different enterprises. IoT is likewise one of  the fundamental mainstays of the modern transformation 4.0. Technological developments and convenience in the Industrial Revolution 4.0 must be connected to the Internet of Things (IoT) application.